The role of mantle inheritance and refertilization during breakup at magma-poor rifted margins: What can we learn from the SW-Australia margin? - Ballay, Mélanie; Ulrich, Marc; Manatschal, Gianreto (Earth and Planetary Science Letters, 2025)
The study of mantle-melt interactions at magma-poor rifted margins, accounting for about half of the world margins, is so far limited by the access to samples. Present concepts are therefore mainly based on studies of the Western Tethys and southern North Atlantic domain, and it remains unclear if they are applicable to other magma-poor rifted margins. Here, we present a study of well-preserved peridotites dredged along the southwestern Australian margin (Diamantina Zone). Our petrological data show that two types of peridotites occur: spinel lherzolite, which represents the inherited subcontinental mantle (SCLM) before the separation of Australia and Antarctica, and plagioclase peridotite formed by syn-rift melt entrapment at low pressure in the plagioclase stability field during mantle exhumation. The observed mantle types as well as the mantle-melt processes identified in the Diamantina peridotites are very similar to those documented in the Alpine-Apennine and Iberia margins. Hence, the Alpine/Iberia model of magma-poor rifted margins may be globally applicable and does not depend on the SCLM inheritance. Remnants of mantle inheritance may be preserved in the refertilized mantle, suggesting a progressive transition from an inherited to a refertilized mantle during breakup. Finally, this study highlights the role of inheritance and refertilization as the main features controlling final rifting and breakup at magma-poor rifted margins.